2005
DOI: 10.1111/j.1740-0929.2005.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal ammonia, urea, volatile fatty acid and lactate levels in dairy cows and their pathophysiological significance during diarrhea

Abstract: Normal fecal samples were taken from lactating cows fed either a total mixed ration (TMR; n = 30) or pasture‐based diet (20) and from dry cows fed mainly on hay (15). Diarrheic fecal samples (n = 51) were collected from 21 sick dairy cows. Fecal analyses of ammonia, urea, lactate and volatile fatty acid (VFA) levels were used to evaluate colonic fermentation. Most normal feces had reasonably neutral pH, however, alkaline feces were observed in diarrheic cows. Although fecal lactate is higher in cows on grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…The concentrations of volatile fatty acids in this study are similar to results obtained in other studies [29]. Correlation analysis showed that a significant positive correlation was observed between the genus Stenotrophomonas and the levels of acetate, propionate, and TVFA (Figure 6).…”
Section: Discussionsupporting
confidence: 90%
“…The concentrations of volatile fatty acids in this study are similar to results obtained in other studies [29]. Correlation analysis showed that a significant positive correlation was observed between the genus Stenotrophomonas and the levels of acetate, propionate, and TVFA (Figure 6).…”
Section: Discussionsupporting
confidence: 90%
“…The centrifuged (2500 g , 10 min) supernatant of the extract was frozen at −30°C until analysis. Lactate and VFAs were analyzed as described previously (Sato & Nakajima 2005). Methanol, ethanol, and i‐ and n ‐propanol of the extracts were determined using a gas chromatography equipped with a flame ionization detector (GC 2014; Shimadzu, Kyoto, Japan) and a column packed with Thermon‐1000 (T‐88; Shinnwa‐kako, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Gas chromatography was also used for analysis of VFAs using crotonic acid as an internal standard. Ammonia and lactate were analyzed by colorimetry using the indophenol reaction and Barker-Summerson method [10], respectively.…”
Section: Animalsmentioning
confidence: 99%